Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00221-005-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to unilateral change in lower limb mechanical properties during human walking

Abstract: To produce successful and safe walking movements, the locomotor control system must have a detailed awareness of the mechanical properties of the lower limbs. Flexibility of this control comes from an ability to identify and accommodate any changes in limb mechanics by updating its internal representation of the lower limb. To explore the ability of the locomotor control system to tune its representation of the lower limb, eight participants performed three 5 min trials (PRE, WEIGHT and POST) of treadmill walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 23 publications
9
87
2
Order By: Relevance
“…While the time course for adaptation to prosthetic alignment has not been previously reported, related studies suggest that both amputees [55] and able-bodied ambulators [56] can quickly adapt (<5 minutes) to novel changes in lower-limb inertia. In fact, a more rigorous investigation of adaptation has shown that able-bodied ambulators can achieve steady-state joint kinematics within 40 to 50 strides [57]. Therefore, we believe the adaptation period used in this study was sufficient to address our hypotheses.…”
Section: Limitationsmentioning
confidence: 83%
“…While the time course for adaptation to prosthetic alignment has not been previously reported, related studies suggest that both amputees [55] and able-bodied ambulators [56] can quickly adapt (<5 minutes) to novel changes in lower-limb inertia. In fact, a more rigorous investigation of adaptation has shown that able-bodied ambulators can achieve steady-state joint kinematics within 40 to 50 strides [57]. Therefore, we believe the adaptation period used in this study was sufficient to address our hypotheses.…”
Section: Limitationsmentioning
confidence: 83%
“…Current measurements indicate that position/angle measurement of the legs 1 http://www.bw.ctw.utwente.nl/research/projects/ via the robot device is not sufficiently accurate for inverse dynamic calculations. However, it appeared accurate enough for a safe implementations of an impedance controller that interferes with a walking subject [26].…”
Section: Discussionmentioning
confidence: 99%
“…A linear mixed model (LMM) for repeated measures was used to compare the error size during the first 10 strides of the adaptation period across the three resistance load conditions. We focused on the first 10 strides of the adaptation period because previous studies suggested that error could be corrected or minimized later in this period [2][3][4]. The stride number (1-10) was treated as a covariate.…”
Section: Data Analysis and Statistical Analysismentioning
confidence: 99%
“…For example, when experiencing a force perturbation resisting leg flexion during the swing phase of gait, subjects initially made larger errors in leg kinematics (e.g., decreased knee flexion) [2]. The error size gradually decreased over time as the central nervous system (CNS) adapted to the force perturbation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation